VD_FINDINFO HC / 2013 / 40 vom 10. Dezember 2012 - VD Tribunal cantonal (2012)
PRESTATION DE PRÉVOYANCE, RENONCIATIONSENS GÉNÉRAL, SIMULATION | 122 CC, 123 CC, 18 CO, 280 al. 3 CPC (CH), 308 CPC (CH), 312 al. 1 CPC (CH)